Honghua Xiaoyao tablet combined with estradiol improves ovarian function in D-galactose-induced aging mice by reducing apoptosis and affecting the release of reproductive hormones: an in vivo study - Su, Chan; Zhang, Ruihong; Zhang, Xiujuan; Feng, Xiaoning; Wu, Qiong; Gao, Yiwei; Hao, Jing; Mu, Yu-lan (Frontiers in Pharmacology, 2024)
Context: It is very necessary to delay ovarian aging and prevent age-related health problems. The active ingredient in Honghua Xiaoyao tablet (HHXYT) has the effects of anti-oxidation, anti-inflammation, immune regulation and so on. Objective: To explore the effect and mechanism of Honghua Xiaoyao tablet on aging model mice. Materials and methods: The aging model was established by intraperitoneal injection of D-galactose in model mice. The mice in the HHXYT-L,M,H group were given 0.3g/kg, 0.6g/kg and 1.2g/kg Honghua Xiaoyao tablet suspension respectively, and the HHXYT-M+E2 group was given 0.6g/kg HHXYT + 0.13mg/kg estradiol valerate for 30 days. In this study, ELISA, HE, Western-blot, IH and TUNEL were used. Results: HHXYT+E2 can improve the gonadal index, estrous cycle of aging mice. In HHXYT-M+E2 group, the level of FSH and LH decreased, while E2 and AMH increased significantly. The number of growing follicles in HHXYT-M+E2 group increased, which was better than that of HHXYT alone. Western-blot results showed that HHXYT-M+E2 group decreased the expression of Bax, cleaved-Parp, cleaved-Casp-3 and CytC molecules and increased the expression of Bcl-2 in ovarian tissue. FSHR expression decreased in model group and increased in HHXYT group. TUNEL staining showed that the number of apoptotic cells in HHXYT group was reduced, and the HHXYT-M+E2 group was the most significantly. Discussion and conclusion: HHXYT can improve the level of sex hormones and increase the number of growing follicles in aging mice. HHXYT-M+E2 group has the best effect, and its mechanism may be related to reducing ovarian granulosa cell apoptosis.